2018
DOI: 10.3892/ol.2018.8200
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated expression of HOXC8 is associated with poor prognosis of cervical cancer

Abstract: Homeobox C8 (HOXC8) is a transcription factor that has been reported to regulate numerous genes associated with tumor progression. However, its function in cervical cancer (CC) remains to be elucidated. In the present study, the expression level of HOXC8 was examined in CC tissues and cell lines using reverse transcription-quantitative polymerase chain reaction and western blot analysis. Additionally, CC cell lines were transfected with small interfering RNAs (siRNAs) to downregulate the expression of HOX8 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…CMs were incubated in 10% CCK-8 (Dojindo, Kumamoto, Japan) that was diluted in normal culture medium at 37 °C until a visual color conversion occurred. The absorbance of each well was measured using a microplate reader (Spectrafluor, TECAN, Sunrise, Austria) at 450 nm [15]. Three individual experiments were performed.…”
Section: Methodsmentioning
confidence: 99%
“…CMs were incubated in 10% CCK-8 (Dojindo, Kumamoto, Japan) that was diluted in normal culture medium at 37 °C until a visual color conversion occurred. The absorbance of each well was measured using a microplate reader (Spectrafluor, TECAN, Sunrise, Austria) at 450 nm [15]. Three individual experiments were performed.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13] HOXC8 is located at chromosome 12 and plays an oncogenic role in human cancers. [14][15][16][17]21,22 Moreover, HOXC8 is regulated by miRNAs such as miR-196s in breast cancer. 17 However, the role of HOXC8 in chordoma remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…14 Numerous studies have investigated the role of homeobox C8 (HOXC8) in human cancers, and found that its expression was dysregulated in cervical cancer, non-small cell lung cancer, breast cancer, and osteosarcoma. [15][16][17] For example, HOXC8 expression was upregulated in cervical cancer and its overexpression promoted cell proliferation. 15 Moreover, HOXC8 was revealed as a trigger for nonsmall cell lung cancer cell proliferation and migration activation through inducing transforming growth factor-b1 expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, abnormally poor expression of TMPRSS11B has been revealed in squamous cell carcinoma 19 . High expression of homeobox C8 ( HOXC8 ) is associated with the poor prognosis of hepatocellular carcinoma, cervical cancer, and ovarian cancer 20–22 . Additionally, abundant expression of colony‐stimulating factor 2 ( CSF2 ) is associated with the poor overall survival and disease‐free survival in colorectal cancer patients 23 .…”
Section: Discussionmentioning
confidence: 88%